2000
DOI: 10.1161/01.res.86.8.827
|View full text |Cite
|
Sign up to set email alerts
|

Bone Sialoprotein and the Paradox of Angiogenesis Versus Atherosclerosis

Abstract: Bone sialoprotein (BSP) is a protein thought to be highly specific for bone. BSP contains an arginine-glycineaspartic acid (RGD) cell attachment sequence involved in osteoclast adhesion to bone matrix via the vitronectin receptor and plays an important role in the early process of bone mineralization and resorption. The study by Bellahcène et al 1 in this issue of Circulation Research indicates that BSP mediates adhesion and chemotactic migration of endothelial cells and promotes angiogenesis, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Bone siloprotein synthesized by the osteoblast-like VSMC has recently been shown to be an angiogenic protein capable of inducing neovascularization by interacting with the alpha v beta 3 integrin [18]. Even more exciting is the finding that the endothelial pericyte is capable of synthesizing this non-collagenous angiogenic factor as well as being related to ossification of atherosclerotic plaques.…”
Section: Vascular Ossification – Calcification (Voc)mentioning
confidence: 99%
“…Bone siloprotein synthesized by the osteoblast-like VSMC has recently been shown to be an angiogenic protein capable of inducing neovascularization by interacting with the alpha v beta 3 integrin [18]. Even more exciting is the finding that the endothelial pericyte is capable of synthesizing this non-collagenous angiogenic factor as well as being related to ossification of atherosclerotic plaques.…”
Section: Vascular Ossification – Calcification (Voc)mentioning
confidence: 99%
“…Many investigators agree that valve calcification is an active inflammatory process. Collagen (tenascin-C) or bone matrix proteins (osteopontin and osteonectin) produced by activated macrophages and vascular cells (10,21) promote neoangiogenesis (22) and are involved in the regulation of calcium deposition in atherosclerotic plaques (21)(22)(23), as well as in cardiac valves (10). In contrast, Mohler et al (12) suggest that dystrophic calcification is a passive degeneration of connective tissue, whereas heterotopic ossification is an active process of abnormal tissue repair.…”
mentioning
confidence: 99%
“… 33 Our results showed that BSP was highly expressed in Yunnan Baiyao II group, which indicated that Yunnan Baiyao at concentration of 100 μg/mL could promote osteoblast maturation, mineralization, and deposition, and promote bone formation. In addition, BSP also played an important role in the process of angiogenesis, and the endothelial cell surface of new capillary endothelial cells could express and recognize BSP, which could support vascular growth in bone matrix calcification, 34 therefore, BSP is closely related to the growth of blood vessels during the bone formation process.…”
Section: Discussionmentioning
confidence: 99%